How Anxious are Turkish EFL Learners? Tolerance of Ambiguity and Self-perceived Communication Competence as Predictors - Mehmet Asmalı (Literacy Trek, 2019)
Foreign language anxiety has already been reported to deteriorate learners' language learning performance. It is closely related to how learners perceive their communication performance in the target language and how tolerant they are when they face ambiguities in foreign language learning. Therefore, the current study investigated learners' foreign language classroom anxiety (FLCA), second language tolerance of ambiguity (SLTA), and self-perceived communication competence (SPCC). The study also aimed to examine the potential predictive power of SPCC and SLTA on Turkish EFL learners' FLCA. Mixed-methodology design was used combining the data gathered from four semi-structured interviews and three different questionnaires. 156 freshmen studying at a Turkish state university enrolled in different departments participated in this study. Descriptive statistics showed that students had a moderate level of FLCA, but low SLTA and SPCC. Multiple regression analyses significantly identified SLTA and SPCC as predicting FLCA. Both independent variables were negatively related to FLCA explaining 26% of the total variance. In the light of the findings, some practical suggestions were put forward both for language teachers and further research.